Loss of TOP3B leads to increased R-loop formation and genome instability. Issue 12 (4th December 2019) - Zhang, Tao; Wallis, Mathew; Petrovic, Vida; Challis, Jackie; Kalitsis, Paul; Hudson, Damien F.
Abstract : Abstract : Topoisomerase III beta (TOP3B) is one of the least understood members of the topoisomerase family of proteins and remains enigmatic. Our recent data shed light on the function and relevance of TOP3B to disease. A homozygous deletion for the TOP3B gene was identified in a patient with bilateral renal cancer. Analyses in both patient and modelled human cells show the disruption of TOP3B causes genome instability with a rise in DNA damage and chromosome bridging (mis-segregation). The primary molecular defect underlying this pathology is a significant increase in R-loop formation. Our data show that TOP3B is necessary to prevent the accumulation of excessive R-loops and identify TOP3B as a putative cancer gene, and support recent data showing that R-loops are involved in cancer aetiology.